4-Methylesculetin ameliorates LPS-induced depression-like behavior through the inhibition of NLRP3 inflammasome - Choudhary, Khushboo; Prasad, Surendra Rajit; Lokhande, Kiran Bharat; Murti, Krishna; Singh, Sanjiv; Ravichandiran, Velayutham; Kumar, Nitesh (Frontiers in Pharmacology, 2023)
The pathophysiology of depression is heavily dependent on inflammation. Evidence suggests that the aetiology of depression is linked with NLRP3 inflammasome-induced inflammation. Therefore, blocking the activated NLRP3 inflammasome may be beneficial for treating depression. Due to the limitations of currently available anti-depressants, it is necessary to develop novel, safe, and affordable drugs for the treatment of depression. A natural coumarin derivative named 4-Methylesculetin (4-MESC) possesses anti-inflammatory activity. However, the role of 4-MESC as an antidepressant has not been elucidated. Therefore, in this study, we explored the antidepressant-like effects of 4-MESC and its underlying molecular mechanism through modulation of the NLRP3 inflammasome. The Docking and Molecular dynamic simulation studies revealed that the 4-MESC has a higher affinity for the NLRP3 PYD. Blood-brain barrier permeability was confirmed by the SwissADME Pharmacokinetic Tool. High doses (50 mg/kg) of 4-MESC significantly reduced immobility duration in TST and FST without changing the mice's overall locomotor activity in the female Swiss albino mice that were subjected to lipopolysaccharide (LPS). LPS-induced pro-inflammatory cytokines such as IL-6 and TNF- were reduced in serum and brain tissue by 4-MESC. 4-MESC's neuroprotective effects are mediated by increased BDNF and decreased cortisol levels. 4-MESC markedly reduced LPS-induced elevated levels of ROS, lipid peroxidation (malondialdehyde levels) and enhanced the SOD activity and glutathione levels, which revealed its anti-oxidant potential against oxidative stress. 4-MESC diminished the expression levels of NF-κB p65, IL-6, NLRP3, caspase-1, gasdermin D, and IL-1β and in the hippocampus. These findings demonstrated that 4-MESC exerted antidepressant-like effects by inhibiting the NLRP3 inflammasome. However, other antidepressant mechanisms also might be involved which require further studies.